Business statistics : Methods and Applications - Meek, Gary E. (Needham Heights, MA : Ginn Press, 1992)
This book is concerned with the application of statistical methods to management and business related areas, this text examines marketing, operations, human resource management, finance and strategy. The overall emphasis is upon student's understanding rather than the mere application of the correct formula.
Includes index.
aia 25/8/17
Loans
Keywords: Commercial statistics; Statistics; United States